DETERMINATION OF THERMAL PROPERTIES OF COFFEE BEANS AT DIFFERENT DEGREES OF ROASTING - Cardoso, Danilo Barbosa; Andrade, Ednilton Tavares de; Calderón, Renso Alfredo Aragón; Rabelo, Mariane Helena Sanches; Dias, Camila de Almeida; Lemos, Isabela Ávila (Coffee Science - ISSN 1984-3909, 2018)
The aim of this study was to determine the main thermal properties of the granular mass of coffee (specific heat, thermal conductivity, and thermal diffusivity) for different degrees of roasting, as well as to model and simulate thermal conductivity at different degrees of roasting. For determination of specific heat, the mixing method was used, and for thermal conductivity, the theoretically infinite cylinder method with a central heating source. Thermal diffusivity was simulated algebraically using the results of the properties cited above and of the apparent specific mass of the product. Thermal conductivity was also simulated and optimized through finite element analysis software. At darker roasting, there was an increase in specific heat and a reduction in thermal conductivity and thermal diffusivity. Comparing thermal conductivity determined in relation to simulated and optimized conductivity, the mean relative error was 1.02%, on average.